Ages of anxiety: historical and transnational perspectives on juvenile justice - Bush, William S.; Tanenhaus, David Spinoza (Youth, crime, and justice series, 2018)
From criminal justice to the social clinic : the role of magistrates in the circulation of transnational models in the twentieth century / David Niget -- The modernization of authority : juvenile delinquents and their caseworkers in post-revolutionary Mexico City / Shari Orisich -- The search for juvenile delinquency in colonial Zanzibar, East Africa / Corrie Decker -- Youth consciousness, delinquency, and the Montreal miracle / Tamara Myers -- Supervising freedom : juvenile delinquency in Paris and Boston in the mid-twentieth century / Guillaume Prissol -- Unclaimed forlorn monsters? : perceptions of youth crime and the limits of juvenile justice reform in Turkey, 1979-2005 / Nazan Iek -- Conclusion : whose children : a comparative anatomy of moral panics / William S. Bush, Texas A&M University-San Antonio, David S. Tanenhaus